2007
DOI: 10.1590/s1676-26492007000200007
|View full text |Cite
|
Sign up to set email alerts
|

Actual bioavailability of divalproex sodium extended-release tablets and its clinical implications

Abstract: Divalproex sodium extended-release dosage form (divalproex-ER) has been promoted as innovative formulation for the treatment of epilepsy and manic disorders, and for migraine headache prevention, with the advantage of being dosing once a day. Due to a significant decreasing in the peak-trough fluctuation of plasma valproic acid levels, in comparison with the twice-daily dosing of conventional delayed-release formulations (divalproex-DR), concentration-dependent side effects would be prevented. However the main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…Patients receiving VPA-ER had fewer central nervous system adverse effects (i.e., fatigue/asthenia, headache, memory loss, and tremor), weight increase, and hair alterations. At present, a large number of pharmacokinetic studies have shown that the significantly decreased peak-trough fluctuation of plasma valproic acid levels and the stable serum concentrations of divalproex contribute to preventing concentration-dependent AEs ( Ieiri et al, 1995 ; Kondo et al, 2002 ; Smith et al, 2004 ; Fagiolino et al, 2007 ), such as central AEs. Nevertheless, the specific reasons for this need to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…Patients receiving VPA-ER had fewer central nervous system adverse effects (i.e., fatigue/asthenia, headache, memory loss, and tremor), weight increase, and hair alterations. At present, a large number of pharmacokinetic studies have shown that the significantly decreased peak-trough fluctuation of plasma valproic acid levels and the stable serum concentrations of divalproex contribute to preventing concentration-dependent AEs ( Ieiri et al, 1995 ; Kondo et al, 2002 ; Smith et al, 2004 ; Fagiolino et al, 2007 ), such as central AEs. Nevertheless, the specific reasons for this need to be further explored.…”
Section: Discussionmentioning
confidence: 99%